2010
DOI: 10.1051/0004-6361/201014202
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of 78 DENIS ultracool dwarf candidates in the solar neighborhood and the Upper Scorpii OB association

Abstract: Aims. We search for new ultracool dwarfs and report here our observations of 78 ultracool dwarf candidates that have been photometrically selected using the DENIS survey point source catalogue. We analyze low-resolution optical spectroscopic observations to estimate spectral types of all candidates. Methods. We derive spectral types for each object using measurements of the PC3 spectral index as defined in Martín et al. They range from M6 to L3. The Hα emission and NaI subordinate doublet (818.3 nm and 819.9 n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 60 publications
4
53
0
Order By: Relevance
“…More precise U V W XY Z data for this object as well as a more expansive census of the β Pic stellar members would help refine the membership. Martín et al (2010) noted that 2MASS J1935−2846 is near the R CrA star forming region on the sky, but our proper motion of (+27.3 ± 0.9, −61.6 ± 1.1) mas yr −1 is inconsistent with the mean of known members, (+5.5, −27.0) mas yr −1 (Neuhäuser et al 2000), and our parallax distance of 70.4 +6.5 −5.5 pc is much closer than the region's best distance estimate of 130 pc (Neuhäuser & Forbrich 2008).…”
Section: Mass J19355595−2846343 (M9 Low-g/m9 Vl-g)mentioning
confidence: 99%
“…More precise U V W XY Z data for this object as well as a more expansive census of the β Pic stellar members would help refine the membership. Martín et al (2010) noted that 2MASS J1935−2846 is near the R CrA star forming region on the sky, but our proper motion of (+27.3 ± 0.9, −61.6 ± 1.1) mas yr −1 is inconsistent with the mean of known members, (+5.5, −27.0) mas yr −1 (Neuhäuser et al 2000), and our parallax distance of 70.4 +6.5 −5.5 pc is much closer than the region's best distance estimate of 130 pc (Neuhäuser & Forbrich 2008).…”
Section: Mass J19355595−2846343 (M9 Low-g/m9 Vl-g)mentioning
confidence: 99%
“…Therefore, LP 655-48 is very likely an old field late-M dwarf. Using the spectra of 28 late-M dwarfs published in Crifo et al (2005) and Phan-Bao & Bessell (2006), we also measured EWs of the Na I doublet at 8183 Å and 8199 Å, which is an indicator for surface gravity of young M dwarfs (e.g., Lyo et al 2004;Schlieder et al 2012), over the range of 8170−8200 Å as described in Martín et al (2010). The uncertainties in the EW measurement were estimated by measuring EWs with different possible continuum levels.…”
Section: Lithium Detection In Five Late-m Dwarfsmentioning
confidence: 99%
“…DENIS1048 (spectral classification M8.5; Henry et al 2004) was identified as a UD in the DENIS survey (Epchtein et al 1997) by Delfosse et al (2001) and, at a distance of 4.00 ± 0.03 pc (Costa et al 2005), is one of the closest known stars. A recent spectroscopic study by Martín et al (2010) shows that it is unlikely to be a brown dwarf. Fuhrmeister & Schmitt (2004) reported a large optical flare and a fast projected rotation velocity of v sin i = 25 ± 2 km s −1 .…”
Section: Observations and Data Analysismentioning
confidence: 99%